Dynamic behavior of compound droplets with millimeter-sized particles impacting substrates with different wettabilities - Xing, Lei; Li, Jinyu; Jiang, Minghu; Zhao, Lixin (Physics of fluids (1994), 2023)
The dynamic behavior of compound droplets, which are made up of a millimeter-sized particle and distilled water, impacting substrates of different wettabilities is investigated via high-speed photography. The effects of the size of the particle within the compound droplet, substrate contact angle, and impact height on the deformation of the droplets and the characteristics of the impact are analyzed. It is found that the collisions of compound droplets with substrates can be classified into four categories based on the observed experimental phenomena that occur during the impact. These categories are referred to as adhesion collision, rebound collision, daughter-droplet collision (or partial rebound collision), and breakup collision. We consider both the impact of water droplets and compound droplets (with one of two different-sized particles) on substrates of different wettabilities. The effects of inertia, surface tension, and adhesion between the substrate and the liquid droplet, and adhesion between the particle and the liquid droplet are considered to explain the different collision phenomena of compound droplets and reveal the evolution mechanism of the droplet morphologies in the experiments. Furthermore, the effects of the height from which the droplet is released and the contact angle of the substrate (i.e., its wettability) on the maximum spreading diameter and maximum jet height of the droplet are presented quantitatively. The effect of the size of the particle within the compound droplet and the substrate contact angle on the dynamic behavior of the compound droplet subject to impact with the substrate is also described.